ANALISIS KONTEN LAGU MELAYU TRADISIONAL DAN MODERN (PEMAKNAAN LIRIK-LIRIK LAGU MELAYU KALIMANTAN BARAT) - Muhammad Asyura (Balai Bahasa Kalimantan Barat, 2018)
This research is qualitative research and documentation study that describes the content type of the form and the trend themes raised in Malay song lyrics in West Kalimantan.Data source this study is of Malay songs that add up to 65songs that come from the five major cultural Malay Malay Pontianak, West Kalimantan, namely Sambas, Ketapang, Sanggau Kapuas Hulu, and which have the particularity of the Malay dialect all its own. The results of this study showed there are 20 songs traditional and modern songs with the theme of 45 and its uniqueness of each. Themes reflected in traditional Malay songs are generally themed history, folklore, and traditional relations. However, there was a shift of theme in the modern Malay songs which began to lead the pride of ethnicity, the potential of natural resources, politics, tourism, and social reasons.